Feto-maternal outcome in term and late term pregnancies following induction of labour with misoprostol - Devi, Phurailatpam Rupabati; Singh, Chirom Pritamkumar; Singh, Y. Ajitkumar; Shullai, Barida S.; Balchand Singh, N.; Soni, Saurabh; Dolma, Sonam; Gautam, Nikita; Priyadarshinee, Lipsa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Induction of labour is the artificial initiation of labour before its spontaneous onset for the purpose of achieving vaginal delivery of the feto-placental unit. It is a common obstetric procedure which is indicated when the benefits to mother or fetus outweigh the benefits of continuing the pregnancy. Most common indication for induction is postdated pregnancy. Methods: Longitudinal Study carried out in department of obstetrics and gynaecology, RIMS, Imphal, Manipur, conducted for duration of two calendar years, with effect from January 2021 in 168 primigravidas who had reached full term or late term pregnancy admitted in ante-natal ward of RIMS, Obstetrics and Gynaecology department. Results: Study was conducted on 168 pregnant women, most of the participants belonged to the age group of 18-34 years (77.9%). Vaginal delivery was the most common mode of delivery (64.8%). Most of the babies (72%) delivered were having birth weight of between 2.5 kg to 3.9 kg. PPH and uterine hyperstimulation are comparatively more in the late term pregnancy as compared to full term pregnancy. Meconium-stained liquor was slightly more in late term pregnancy group as compared to full term pregnancy. Babies delivered by full term pregnant women were having better APGAR score in 1 minute and 5 minutes than the babies delivered by late term pregnancy. Conclusions: Late term Pregnancy is comparatively common in low socio-economic group. The CS rate is comparatively high in Late term pregnancy as compared to Full Term Pregnancy. Poor APGAR score is highly associated with Late term Pregnancy outcome.